2020
DOI: 10.1021/jacs.9b11836
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization in Alkynyl-Protected Gold Nanoclusters

Abstract: We report the controlled synthesis and structures of two isomeric gold nanoclusters, whose compositions are determined to be Au 23 (CCBu t ) 15 (denoted as Au 23 -1 and Au 23 -2) by single-crystal X-ray diffraction and matrixassisted laser desorption ionization time-of-flight mass spectrometry. This is the first time isomerism is discovered in alkynyl-protected gold nanoclusters. The metal-toligand ratios in these two clusters are different from known Au n (SR) m systems and have not been observed in the Au x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 52 publications
(59 reference statements)
5
110
0
Order By: Relevance
“…11,12 With the availability of single crystal X-ray structures, 13,14 extensive attention has been paid to the role of ligands in the syntheses and photophysical properties of gold nanoclusters with different nuclearities. 15,16 To obtain novel gold clusters with different photophysical properties, organic ligands such as thiols, phosphines and alkynes have been widely exploited in the syntheses of gold nanoclusters (Au n ) such as Au 8 , 17,18 Au 9 , 19 Au 11 , 20,21 Au 13 , [22][23][24][25][26][27] Au 18 , 27,28 Au 20 , 29,30 Au 22 , 31,32 Au 23 , 33 Au 24 , 34 Au 25 , 35,36 Au 32 , 37 Au 37 , 38 Au 44 , 39 Au 52 , 40 Au 55 , 41 and Au 102 . 13 Among all of the gold nanoclusters that have been structurally characterized, icosahedral Au 13 nanoclusters have been more extensively studied due to their highly symmetrical structure and prominent photoluminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 With the availability of single crystal X-ray structures, 13,14 extensive attention has been paid to the role of ligands in the syntheses and photophysical properties of gold nanoclusters with different nuclearities. 15,16 To obtain novel gold clusters with different photophysical properties, organic ligands such as thiols, phosphines and alkynes have been widely exploited in the syntheses of gold nanoclusters (Au n ) such as Au 8 , 17,18 Au 9 , 19 Au 11 , 20,21 Au 13 , [22][23][24][25][26][27] Au 18 , 27,28 Au 20 , 29,30 Au 22 , 31,32 Au 23 , 33 Au 24 , 34 Au 25 , 35,36 Au 32 , 37 Au 37 , 38 Au 44 , 39 Au 52 , 40 Au 55 , 41 and Au 102 . 13 Among all of the gold nanoclusters that have been structurally characterized, icosahedral Au 13 nanoclusters have been more extensively studied due to their highly symmetrical structure and prominent photoluminescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to thiolates, many other organic ligands have been exploited to synthesize atomically precise metal NCs, due to their diverse binding modes and binding strength with metal centres. Such organic ligands of current interest include phosphines, [258][259][260] hydrides, [261][262][263][264] alkynyls, [265][266][267][268] N-heterocyclic carbenes, [269][270][271] carboxylates, 219,272,273 and solvent molecules. 219,[272][273][274][275] In particular, recent ndings have shown that organic ligands with relatively low binding affinity to Ag (e.g., CF 3 COO À and CH 3 CN) can be replaced by bridging ligands (e.g., 4,4 0 -bypyridine), further cross-linking mixed-ligand-protected Ag NCs into a 3D network reminiscent of MOF structures.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, monolayer‐protected metal nanoclusters (NCs) have gradually gained much attention because of not only their atomically precise aesthetical structures, [ 1 ] but also their wide variety of applications, such as luminescence, [ 2 ] chirality, [ 3 ] cell imaging, [4] catalysis, [5] and electrochemistry. [6] Particularly, photoluminescence (PL) is one of the most explored functions.…”
Section: Background and Originality Contentmentioning
confidence: 99%